Aesthetic study of pun in Leili and majnoon Nezami Ganjavi - Ayob Omidi; Omid Jelodarian (مطالعات زبانی و بلاغی)
Pun is one of the most important figures of speech and tricks that link Azerbaijani style poetry to its true essence, beauty. Nezami Ganjavi is one of the most prominent Persian language poets who has been able to make use of all of his pun capacities in musical and aesthetic richness of his works. In rhetorical books and stylistics, despite the presentation of various types of division, there has been little mention of aesthetic functions. Therefore, in the present article, with a descriptive-analytic approach, while presenting the exact frequency of puns in the poetry of Leili and Majnoon, Nezami's skill and ability to utilize various functions of the genus is analyzed and evaluated. According to a total of 1964 studies, a variety of pun were found in Leili and Majnoon, of which the pun mozare with a frequency of 35.9 and pun lahagh with a frequency of 31.3 were the best areas for Nezami's art. The result of this research suggests the creativity and diversity of pun's functions in the context of Nezami's poems like: strengthening the inner and outer music of the work, verbal and semantic coherence of speech, the literary resolution of the audience due to the understanding of the semantic relations of the components of the word, an artistic companion to other figures of speech(repetition, alliteration, allusion, antithesis) in a couplet.Keywords: Pun, Figures of sound, Rhetoric, Nezami Ganjavai, Leili and Majnoon.